068 Effect of low dose adjunctive perampanel in adults and adolescents with focal- onset seizures. Issue 9 (12th August 2022) - Giallonardo, Anna Teresa; Aguglia, Umberto; Goldman, Samantha; Chiacchiaretta, Martina; Gentile, Anna; Patten, Anna
Abstract : Background: We report a post hoc analysis of the efficacy and safety of low dose adjunctive perampanel 4 mg/day in adults and adolescents from A Mirroring Clinical Practice Study in Italy (AMPA; NCT04257604 ). Methods: AMPA was a prospective, observational study in patients aged ≥12 years with focal-onset seizures (FOS). Patients were prescribed adjunctive perampanel per the approved indication. Seizure diaries and treatment-emergent adverse events (TEAEs) were verified at baseline and study visits. The primary endpoint was change from baseline in seizure frequency/28 days at Month 6. Secondary endpoints included: 50% and 75% responder rates, seizure-freedom rates, retention rates and safety (≤12 months). Results: Of the 234 patients who received adjunctive perampanel, 62 (26.5%) received a modal peram- panel dose of 4 mg/day and were included in the Safety Analysis Set. The 6-month median reduction from baseline in all-seizure frequency was 55.4% (95% confidence interval, 31.7%-90.3%). The 12-month 50% and 75% responder, seizure-freedom and retention rates were 57.1%, 46.9%, 26.0% and 46.8%, respec- tively. TEAEs occurred in 50% of patients; the most common TEAE was dizziness/vertigo (17.7% [n=11]). Conclusions: Adjunctive perampanel at 4 mg/day is efficacious and safe in adult and adolescent patients with FOS in a real-world clinical setting. Funding: Eisai s.r.l.